2007
DOI: 10.1890/06-0442
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Interactive Effects of Enemies and Mutualists on Plant Performance: A Meta-Analysis

Abstract: Abstract. Plants engage in multiple, simultaneous interactions with other species; some (enemies) reduce and others (mutualists) enhance plant performance. Moreover, effects of different species may not be independent of one another; for example, enemies may compete, reducing their negative impact on a plant. The magnitudes of positive and negative effects, as well as the frequency of interactive effects and whether they tend to enhance or depress plant performance, have never been comprehensively assessed acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 36 publications
15
223
2
Order By: Relevance
“…For the ERH, not only were initial similarity of the herbivore and the microbe to the plant significant factors in determining plant invasion success, but the interaction between microbe and herbivore was as well. This mirrors empirical studies that have found non-additive affects when investigating PMI interactions (Morris et al 2007;Bennett 2013). This is most likely related to the plant having a harder time invading because benefits gained from being similar to the microbe are canceled by the increased similarity to the herbivore under the BRH.…”
Section: Discussionsupporting
confidence: 76%
“…For the ERH, not only were initial similarity of the herbivore and the microbe to the plant significant factors in determining plant invasion success, but the interaction between microbe and herbivore was as well. This mirrors empirical studies that have found non-additive affects when investigating PMI interactions (Morris et al 2007;Bennett 2013). This is most likely related to the plant having a harder time invading because benefits gained from being similar to the microbe are canceled by the increased similarity to the herbivore under the BRH.…”
Section: Discussionsupporting
confidence: 76%
“…Damage treatments, which mimicked the natural timing of A. vittatum feeding in this system, may have occurred so early in the plants' development that the resulting resource loss was more than the plants could tolerate. In some cases, mutualists can mitigate the negative impacts of plant enemies such as herbivores (Morris et al 2007), although this did not occur with C. sativus pollinators. In agricultural systems, cultivating mutualisms has been proposed as a method to increase yields and counteract the negative effects of plant damage (Kremen et al 2002, Strauss andMurch 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Additional interactions between other groups (e.g., between above-and belowground pollinators; Barber et al 2011) are possible but beyond the scope of this study, as they would require additional factorial manipulations. Nonetheless, such experiments manipulating multiple interactors will be necessary in the future to quantify the contributions of indirect feedbacks to net plant effects as well as to address the possibility of nonadditive effects among community members (Morris et al 2007). …”
Section: Indirect Effects On Mutualistsmentioning
confidence: 99%
“…We based our analyses of multiple interacting climate change variables on an underlying multiplicative model, as opposed to a more conservative additive model [74], because multiplicative models are more ecologically realistic representations of interacting effects [75] and the log response ratio itself is based on a multiplicative model [76]. Interaction effects were classified as multiplicative (the null hypothesis) if the 95% CI around the interaction effect size (L ab ) contained zero.…”
Section: Effect Size Calculationsmentioning
confidence: 99%